USE OF MILIACYLЕ AND PHYSICAL METHODS IN THE TREATMENT OF TROPHIC ULCERS OF LOWER LIMBS - B. G. Nuzov; A. A. Stadnikov; O. B. Nuzova (Креативная хирургия и онкология, 2017)
The clinical studies included 340 patients with trophic ulcers in lower limbs. It is for the first time that the therapeutic efficacy of local application of Miliacyle combined with magnetolasertherapy has been studied in 124 patients with trophic ulcers (experimental group). The patients of the control group I (84 patients) were treated with topically applied Miliacyle and laser radiation. The patients of control group II (80 patients) were treated only with Miliacyle. In the control group III (52 patients) the 1% solution of Dioxydinum and Oleum Hippopheae were used. In some patients of each group only conservative therapy was used, and some patients underwent preoperative treatment prior to autodermaplasty and operations on veins of lower limbs. On the basis of clinical and morphological studies it is found that the process of ulcer healing occurs most favorably as result of combined use of Miliacyle and magnetolasertherapy.